Integrating Dadiah as a Theme in Science Education to Promote Sustainable Development Goals (SDGs) for Junior High School Students - Suci Indah Putri; Widya Rahmatika Rizaldi (Equator Science Journal, 2024)
Dadiah is a traditional food from the Minangkabau ethnic group of West Sumatra. Dadiah is made from buffalo milk which is fermented in bamboo and left for several days to form a yogurt-like structure. In addition, it is not uncommon for traditional foods that exist in various regions to have high nutritional value and are very good for health as well as through natural manufacturing and processing processes. Some of the sustainability goals are goals to build awareness of healthy living, healthy food sources, and responsible production processes. Thus, this traditional food has a very high potential to implement ESD. This traditional food can be used as a contextual learning resource that can support ESD values. In this study, the content analysis method was used to explore the potential of scientific concepts and ESD values based on kinds of literature. The criteria for content analysis are the relevance to scientific concepts, alignment with ESD values, and the coverage of Sustainable Development Goals (SDGs). There are the curriculum, textbooks, and sources from UNESCO about SDGs. This study showed that there are four basic competencies in science learning that are related to Dadiah as the theme. In addition, Dadiah can cover the five goals of the SDGs (goals number 2, 3, 8, 12, and 15) and can stimulate the achievement of sustainable key competencies in learning. Based on the results of this study, Dadiah which is a traditional food has the potential to be implemented in science learning to achieve Sustainable Development Goals.